Carbon dots with light-responsive oxidase-like activity for colorimetric detection of dopamine and the catalytic mechanism - Jia, Zhenzhen; Liu, Yuna; Cheng, Liangliang; Deng, Zhichao; Zhang, Mingzhen; Tuo, Hang (Frontiers in Chemistry, 2023)
Introduction: Dopamine is one of the most significant neurotransmitters and plays an important role in the management of cognitive functions such as learning, memory, and behavior. The disorder of dopamine is associated with many major mental diseases. It is necessary to develop selective methods for the detection of dopamine. Methods: In this work, carbon dots (CDs) were synthesized by a solvothermal route using glutathione, L-histidine, and formamide as sources. Results: Under light irradiation, The CDs convert dissolved oxygen to singlet oxygen (1O2), which could oxidize TMB. When reduced dopamine was present, it suppressed the catalysis of CDs, then the absorption of the CDs-coupled TMB complex at 652 nm was diminished. Furthermore, it was revealed that the surface groups including hydroxyl, amino, carbonyl, and carboxyl groups of CDs were related to their light-responsive catalytic activity by surface modification. In the range of 0.5-15 μM, the CDs could afford a LOD of 0.25 μM for dopamine detection with fine linearity, also showing good selectivity. Discussion: The results from fetal bovine serum indicated the good applicability of the CDs in the determination of dopamine.